Tendency of employment chosen among Faculty of Plantation and Agrotechnology (FPA) student according to their Cumulative Grade Point Average (CGPA) / Nur Atiqah Ismail and Nordiana Ibrahim - Ismail, Nur Atiqah; Ibrahim, Nordiana (Faculty of Plantation and Agrotechnology, 2018)
As nothing is persistent in the universe same choosing employment is ongoing process through the whole life of a person. These treatise is present in order to determine relationship factors influencing career choice by student and CGPA. Second, is to determine sector of employment preferred by a student. This study was conducted at UiTM Jasin Campus, Melaka, which involving of FPA student. The researcher use questionnaire in order to determine data regarding of the factors employment chosen and CGPA of a student. Equally important, the method use is simple random sampling. All of data that has been collected from respondent are analyses by using SPSS software. To the extent that, the findings show field of interest, personality and influential people has relationship toward the CGPA of FPA students. But at the same time, the personality is the one variable that show that strong significant relationship toward influencing CGPA of a students. Indeed, through the survey that has been carried out, 20.2% student agree to choose agriculture as a field that they want participate once graduated. The finding from this treatise can help the student make better decision about their future employment. Usually, most of student still unsure about the future employment or unable to make a choice between two types of employment. Thus, the student supposedly to expose themselves with tool that help them make a better decision. Namely, career tests, career counselling, job fairs and job shadowing. Early exposition will encourage student to study hard. Thus, this can prevent student from giving up to achieve their dream because of they currently studying in different field.